ACTA ORIENTALIA VILNENSIA EXCHANGE PROGRAMME - Vilnensia 2005 6 (2), Acta Orientalia Orientalia (Acta Orientalia Vilnensia, 2005)
The Editors of the Acta Orientalia Vilnensia in co-operation with the library of the Centre of Oriental Studies at Vilnius University highly welcome a regular exchange of scholarly periodicals in the field of Asian and Middle East Studies. For the suggestions related to periodical exchange, please contact the Editorial Board Secretary.Periodicals received under the Acta Orientalia Vilnensia Exchange Programme by 2007: Acta Asiatica. Bulletin of the Institute of Eastern Studies (The Toho Gakkai. The Institute of Eastern Culture)Acta Orientalia et Africana Gothoburgensia (Goteborg University)Annals of the Bhandarkar Oriental Research Institute (Bhandarkar Oriental Research Institute)Archív Orientální (Academy of Sciences of the Czech Republic)Asian Folklore Studies (Nanzan University)Asiatische Studien / Études Asiatiques (University of Zurich)Bulletin of the Deccan College Post-Graduate and Research Institute (Deccan College Post-Graduate and Research Institute)Cracow Indological Studies (Institute of Oriental Philology, Jagiellonian University)East and West (Italian Institute for African and Asian Studies)Folia Orientalia (Polish Academy of Sciences)Hosei University Bulletin of Institute of International Japan-Studies (Hosei University)Indologica Taurinensia (International Association of Sanskrit Studies)International Journal of Dravidian Studies (Dravidian Linguistics Association)Japanese Journal of Religious Studies (Nanzan University)Journal of the International College for Postgraduate Buddhist Studies (International College for Postgraduate Buddhist Studies)Linguistic and Oriental Studies from Poznan (Adam Mickiewicz University)Monumenta Serica. Journal of Oriental Studies (Monumenta Serica Institute)Orientalia Suecana (Uppsala University)Pandanus (Charles University)PILC Journal of Dravidic Studies (Pondicherry Institute of Linguistics and Culture)Rocznik Orientalistyczny (Polish Academy of Sciences)Studia arabistyczne i islamistyczne (Warsaw University)Studia indologiczne (Warsaw University)Studia Orientalia (Finish Oriental Society)Wiener Zeitschrift für die Kunde Südasiens (University of Vienna)